Economic figures of apple production at national level of Hungary - Felföldi, J.; Ványi, N.; Nyéki, J.; Szabó, Z.; Soltész, M. (International Journal of Horticultural Science, 2011)
Apple is the most important fruit in Hungary, despite of that, it is a paradox that during the last years, apple growing was the most unsuccessful enterprise among the prosperous ones in the country. The real cause of regression was unequivocally the low price, which could be obtained and the inadequate structure of apple varieties. A heavy problem is still the overweight of the quality doomed to supplying the processing industry instead to the fresh consumption. In order to improve the conditions, we aimed the economic analysis of the five year long period, 2005-2009, to trace the changes involving values and costs of production, income and all conditions combined with this activity. The data presented in the paper are means of a heterogeneous population of values, which cannot be utilised for immediate use in management, but they may reveal the challenges and tendencies of that branch in economics.